Mineral supplementation protected intestinal health in Litopenaeus vannamei by alleviating the immune response and oxidative damage caused by high-level of Clostridium autoethanogenum protein - Jiahao Song; Chaozhong Zheng; Qi Hao; Jiayi Huang; Wencheng Huang; Shuyan Chi; Beiping Tan; Wen Huang; Shiwei Xie (Aquaculture Reports)
This study investigates the impact of dietary mineral supplementation in Clostridium autoethanogenum protein (CAP)-containing low-fishmeal diets on growth, lipid metabolic profile, and immune and antioxidant capacity in Litopenaeus vannamei. Three diets were formulated in this experiment. The positive control group (PC) was a high fishmeal protein diet with 25 % fish meal, and CAP was used to replace the low fish meal diet (NC) with 50 % fish meal (12.5 % fishmeal) in the PC group. The third group was added minerals (Mg, Fe, Mn and Se) (HM) in the NC diet. Each group contained 160 shrimp, divided into 4 replicates (initial weight: 1.79 ± 0.02 g). The results showed that after fishmeal was replaced by CAP, the growth performance and antioxidant capacity of shrimp decreased. Challenges to lipid metabolism homeostasis were also observed. Transcriptional analysis revealed upregulation of innate immune genes (dorsal, relish, litaf) in the NC dietary group compared to other groups. After mineral supplementation, antioxidant and immune capacity were enhanced. In addition, correlation analysis showed that there was a significant interaction between midgut morphology and immune genes. In conclusion, mineral supplementation can partially alleviate the oxidative stress and immune imbalance caused by the replacement of fish meal with CAP, but has limited effects on the growth of shrimp.